TELAAH MAKNA PENDIDIKAN ISLAM DALAM RITUAL ADAT LEBARAN TINGGI PADA KOMUNITAS ADAT “WETU TELU” DI BAYAN LOMBOK UTARA - Lalu Habiburrahman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
This research focuses on the study of the study of the meaning of Islamic education in the traditional rituals of Lebaran Tinggi in the “wetu telu” traditional community in Bayan, North Lombok. The problem in this research is to examine and examine the meanings of Islamic education in the traditional rituals of Eid al-Fitr in the Bayan community, the series of ritual implementations, and the function of the traditional rituals of Lebaran Tinggi. This study uses a study of social identity from an educational perspective or the meaning of Islamic education in rituals. The method used in analyzing this research problem is a descriptive method with field research techniques. The Adatlebaran Tinggi ritual specifically describes the ritual traditions and series of customs of the local Bayan community which are carried out to maintain ancestral heritage for indigenous peoples and serve to show the existence and standard of living of the communal who carries out this tradition.